User-Librarian Interaction in Reference Service: A Conceptual Model and Case Study - Pratap Lingam, P. (Journal of Information and Knowledge, 1980)
A three-dimentional conceptual model of Reference and Information Service is presented. In particular, the professional and behavioural aspects in information finding process is discussed. The strategy and tactics in user-librarian interaction are highlighted. A case study of interactions is presented and analysed. Application of "transactional analysis" for improving skills of librarians in rendering reference and information service is discussed. Suggests application of studies in communication science for enhancing productivity in information retrieval process.